Behavioral and Structural Determinants of the HIV/AIDS Epidemic Surge Among Urban Adolescents (15–24 Years) - Robinson Baldwin Henrickson; Lisa Tasian; Miguel Surena Fortes; Teresa Concepcion (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
The Philippines is currently facing a rapid surge in HIV/AIDS cases. Adolescents aged 15 to 24 are the primary demographic driving this national trend. To understand the underlying risk factors, we conducted a descriptive quantitative study between January and April 2025. Primary data were gathered through structured surveys from 850 adolescent respondents across Metro Manila, Cebu, and Davao City. Alongside these surveys, qualitative interviews were conducted with 50 healthcare workers. We then compared these primary findings against official secondary registries from the Philippine Department of Health. The combined data revealed an exponential curve in new youth infections. Adolescents now account for nearly 30% of all national cases. In 2024 alone, new infections surged by 25.5%. Geographically, these cases are heavily concentrated in urban centers, with males representing 82% of the affected group. Various behavioral determinants directly drive this shift. Major factors include unprotected sexual encounters (72%), heavy exposure to uncurated adult content on social media and dating apps (88%), and low overall health literacy (45%). Early clinical intervention is also severely hindered by structural barriers. Pervasive social stigma discourages 65% of youth from seeking initial diagnostic tests. Furthermore, this reluctance is worsened by legal mandates that require minors to secure parental consent before testing. In conclusion, the acute vulnerability of Filipino youth stems from a mismatch between rapid digital transformations and rigid policy constraints. Immediate policy reforms are urgently needed to curb this trajectory. We recommend the decriminalization of independent self-testing for minors, the rollout of aggressive digital health campaigns, and the decentralization of clinical services to bypass hospital-level stigma. Moving forward, this framework should be expanded beyond major cities. Future research must urgently investigate transmission dynamics and potential spillover effects into rural agricultural regions.